Implementasi Kebijakan Pengembangan Ekowisata dalam Meningkatkan Perekonomian Daerah : (Studi pada Destinasi Wisata Gombengsari Kabupaten Banyuwangi) - Gaffar Rahman, Auliya; Hidayati, Nuri (Jurnal Ilmiah Administrasi Publik, 2023)
This study focuses on 3 main aspects of the implementation of ecotourism development policies in Gombengsari Village, Banyuwangi Regency. This research limits the implementation study before the Covid 19 pandemic. From the theoretical aspect, this study uses Edward III's theory as the main reference theory and ecotourism theory. This research uses qualitative-descriptive research methods. Primary data sources are interview results and secondary data sources are documents. data analysis techniques using Miles and Huberman data analysis. The results obtained show that there are several obstacles such as the absence of monitoring and evaluation of training programs by Dinas Kebudayaan dan Pariwisata of Banyuwangi Regency and low operational budgets in regional tourism development. But in general, the implementation that occurs is good, manifested in the form of tourism development in both tourist destinations and tourism support industries.